Development of a problem-based learning teaching module to facilitate students' mathematical communication ability - Ipu Anandari Silsiamar; Putri Yuanita; Susda Heleni (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2026)
Mathematical communication ability is one of the important abilities in mathematics learning because it enables students to express mathematical ideas, represent contextual problems into mathematical models, use appropriate mathematical symbols, and write conclusions from problem-solving. However, students’ mathematical communication ability remains relatively low, especially in solving contextual problems related to statistics. This study aimed to develop a Problem-Based Learning teaching module on measures of central tendency and data dispersion that is valid and practical for facilitating students’ mathematical communication ability. This research used a Research and Development approach with the 4D model, consisting of define, design, develop, and disseminate stages. The teaching module and its supplementary student worksheets were validated by three experts and evaluated through one-on-one evaluation, small group trial, and large group trial at SMP Negeri 3 Mandau. The validation results showed that the teaching module obtained an average score of 3.65 and was categorized as very valid, while the student worksheets obtained an average score of 3.61 and were also categorized as very valid. The practicality results showed that the student worksheets obtained an average score of 3.52 in the small group trial and 3.53 in the large group trial, both categorized as very practical. These findings indicate that the developed teaching module meets the criteria of validity and practicality and can be used as a learning resource to facilitate students’ mathematical communication ability.